(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Purpose: Forensic anthropology involves the examination of human remains for medicolegal purposes. Age, sex, and stature are critical aspects of identifying unknown individuals. Stature estimation can be achieved through various morphometric indices. The aim of the present study was to estimate and correlate the stature of an individual using odontometric and craniofacial indices. Methods: The study included 100 subjects from the Haryana population. Odontometric and craniofacial measurements were taken, and different indices were calculated using standardized formulas. Data analysis was conducted using SPSS (Statistical Package for Social Science). Results: A significant correlation was observed between odontometric and craniofacial indices and an individual’s stature. The left central incisor index and right canine index showed better correlation with stature in both males and females. The highest variance was observed with the nasal index in both genders. Conclusions: The findings indicate a positive correlation between odontometric and craniofacial indices and stature. These results can aid forensic investigations by improving methods of identification.